Indoloindole as a new building block of a hole transport type host for stable operation in phosphorescent organic light-emitting diodes. Issue 20 (30th April 2019) - Lee, Ha Lim; Lee, Kyung Hyung; Lee, Jun Yeob
Abstract : An organic material for application as a p-type host of phosphorescent organic light-emitting diodes was newly developed using an indoloindole moiety as a hole transport unit. Abstract : An organic material for application as a p-type host of phosphorescent organic light-emitting diodes was newly developed using an indoloindole moiety as a hole transport unit. The indoloindole derived organic material showed better hole transport properties than a common carbazole based organic material. The good hole transport property of the indoloindole derivative allowed its use as a p-properties host material in an exciplex type mixed host of phosphorescent organic light-emitting diodes. The new host extended the lifetime of yellow phosphorescent OLEDs by more than 10 times compared with a conventional p-type host while achieving a similar external quantum efficiency.